Growth in the neonatal period after repeat courses of antenatal corticosteroids: data from the ACTORDS randomised trial. Issue 2 (27th July 2011) - Battin, Malcolm; Bevan, Coila; Harding, Jane
Abstract : Objective: To determine the effect of repeated antenatal corticosteroids on postnatal changes in weight, linear growth and head circumference. Methods: Mothers who entered the repeated dose of antenatal steroids (ACTORDS) trial were randomised to additional weekly steroid or placebo. Infant occipital-frontal head circumference, weight and crown-heel length were measured at birth and weekly for 4 weeks or until discharge, whichever was later. Lower leg length was measured using a knemometer daily for the first week, then thrice weekly. Results: Of 145 babies studied (77.5% of the ACTORDS study infants from this centre), 70 were exposed to repeated antenatal steroids and 75 to placebo. There were no significant differences in prerandomisation demographic and pregnancy data. The mean gestational age at ACTORDS entry was 28.7 weeks and at birth was 31.4 weeks. The mean birth weight was 1618 g. There were no significant differences in postmenstrual age, weight, length or head circumference, nor in z-scores for these measurements, at birth, 4 weeks or discharge. In the first 2 weeks after birth, babies in both groups showed a decrease in z-scores for weight and length. After week 2, growth improved in both groups but babies exposed to repeat antenatal corticosteroids grew more rapidly, as measured by weight gain, increasing head circumference and increasing lower leg length knemometry. This rapid growth was most apparent around weeks 3–5 after birth. Conclusion: Babies exposed to weekly doses of repeat antenatal corticosteroids demonstrate postnatal growth acceleration 3–5 weeks after birth.